PENGARUH KEPUASAN KERJA DAN IKLIM ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) KARYAWAN PADA PT. TRUBUS SWADAYA DEPOK - Waspodo, Agung AWS; Minadaniati, Lussy (Fakultas Ekonomi, Universitas Negeri Jakarta, 2012)
The purpose of the research are: 1) To know description for job satisfaction, organization climate, and OCB at PT. Trubus Swadaya. 2) Test empirically influence of job satisfaction towards OCB at PT. Trubus Swadaya. 3) Test empirically influence of organization climate towards OCB at PT. Trubus swadaya. 4) Test empirically influence of job satisfaction and organization climate towards OCB at PT. Trubus Swadaya. The analysis implemented in this research are simple regression and multiple regression analysis. The method of this research is simple random sampling, that taken 59 employees, while data collecting by using quitionaire and cultivated using SPSS 16.0. The result of t test for job satisfaction is 2.386, and the signification is 0.020. This shows that there is an effect between job satisfaction towards OCB. The result of t test for organization climate is 2.288, and the signification is 0.026. This shows that there is an effect between organization climate towards OCB. The result of F test is 5.196, and the signification is 0.009. This shows that there is an effect between job satisfaction and organization climate towards OCB. The result of R2 is 0.157 or 15.7%. It means OCB is affected by job satisfaction and organization climate as much as 15.7%. Keywords: job satisfaction, organization climate, OCB